Early distant progression in adult Histone-3 K27-altered diffuse midline gliomas - Graßl, Niklas; Suwala, Abigail Kora; Keßler, Tobias; Bunse, Lukas; Mildenberger, Iris; Breckwoldt, Michael O.; Ratliff, Miriam; Brehmer, Stefanie; Herold-Mende, Christel; Etminan, Nima; Wick, Wolfgang; Sahm, Felix; et al. (Journal of neuro-oncology, 2026)
H3 K27-altered diffuse midline glioma (DMG) is a molecularly defined, highly aggressive tumor entity since the 2016 revision of the World Health Organization (WHO) classification of tumors of the central nervous system (CNS). It has been most extensively characterized in children and adolescents and continues to pose significant challenges to treating physicians due to its growth along the midline structures of the brain and its ability to progress distantly leading to poor prognosis. Clinical and molecular determinants of distant progression and its impact on patient survival particularly in adults have not been thoroughly characterized.
Gesehen am 16.02.2026